INCREASING THE THE ABILITY WRITING SHORT STORIES THROUGH METACOGNITIVE STRATEGIES - Wardiah, Dessy (Jurnal Dosen Universitas PGRI Palembang)
ABSTRACTÂ The objective of this research is to find the increasing of the process and the result studentâs short story writing through metacognitive strategy in language and Indonesia Literature Study Programme FKIP-PGRI University of Palembang. This research uses action research method which is done through planning, action, observation, and reflection. This research was conducted through three cycles, from the result of learning process is found that students have been able to make a planning, monitoring, evaluation and revising according to metacognitive strategy cycle, during their time in writing short story task. This research find out that there had been an increased from the short story writing result in every of its cycle. On the first cycle, there are 8 (eight) students who accomplished the task, with average score is in 64,16. On the second cycle, it showed a significant increased, there were 29 (twenty nine) students who accomplished and 9 (nine) students have not accomplished the task, with average score is ini 72, 18. And the third cycle, there were 38 (thirty eight) students who accomplished the task in the short story writing learning process with average score was in 77,05.Â Keywords: Writing Ability; Short Story; Metocignitive Strategy.